اختلاف الإمام الكسائي مع النحاة الآخرين في النحو - Muhammad Rafif Irfan; Fakhrurozi; Ade Muhammad Ritonga; Abdulfattah Esmail Abdullah Ahmed (PPPBA, 2024)
Abstract The research question is: What are the differences between Imam Al-Kisai and other grammarians in Nahw (Arabic grammar)? This research is comparative using a qualitative approach. The comparative method aims to compare the value of one or more independent variables across two or more communities, individuals, different times, or a combination of all these factors. This research is library research, allowing the researcher to explore and analyze relevant and appropriate written sources, such as books, articles, and other documents, to support a comprehensive understanding of the research topic. The findings of this research are: The differences between Imam Al-Kisai and other grammarians in Nahw include the following issues: the subject of the noun occupied by another, whether